2013
DOI: 10.1080/17450101.2013.784530
|View full text |Cite
|
Sign up to set email alerts
|

Performing Expatriate Mobilities in Kuala Lumpur

Abstract: Research focusing upon expatriates in Asia has been geographically sporadic in nature and has typically centered upon those based in China, Hong Kong or Singapore. Focusing on Kuala Lumpur this research analyses the experiences of expatriates via the notion of automobilty by critically observing their preferred modes of travel and the importance their car journeys play in overcoming problems in Malaysia. While a growing body of research has centered on expatriates' integration into new surroundings, these them… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 54 publications
0
18
1
Order By: Relevance
“…In terms of tourism mobilities we argue that the action of travel may be not only to serve a particular purpose but can also act as an integral feature of many tourists' experiential demands (see Bauman, 1998;Butler and Hannam, 2012, 2013a, 2013bMohktarian and Salomon 2001). What transports a tourist can therefore considerably shape or alter the overall tourist experience (Edensor, 2007;Huijbens and Benediktsson, 2007;Larsen, 2001).…”
Section: Automobilitiesmentioning
confidence: 99%
See 3 more Smart Citations
“…In terms of tourism mobilities we argue that the action of travel may be not only to serve a particular purpose but can also act as an integral feature of many tourists' experiential demands (see Bauman, 1998;Butler and Hannam, 2012, 2013a, 2013bMohktarian and Salomon 2001). What transports a tourist can therefore considerably shape or alter the overall tourist experience (Edensor, 2007;Huijbens and Benediktsson, 2007;Larsen, 2001).…”
Section: Automobilitiesmentioning
confidence: 99%
“…Beckmann (2001: 598) suggests that society's increasing usage of motor vehicles has transformed roads to become -grounds of battle‖, as space is increasingly contested. Indeed, the car's promise of freedom and adventure can be ironically hindered by the car, as other road user curtail driving experiences in the form of traffic congestion and via the poor and even dangerous driving techniques of other drivers (Taylor, 2003;Butler and Hannam, 2013a). As…”
Section: Automobilitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Dennis and Stroh (1993) shared a study of American expatriates, who reported that an education system, language, lifestyles, racial, religious, ethnic groups and organizations internal rivalries are the contributing factors in the work-family difficulties for sojourns in Kuala Lumpur. In addition, transportation preferences in Kuala Lumpur were found unfavourable, thus causing the expatriates" frustration (Butler and Hannam, 2014). Basically, cross-cultural adjustment and adaptation involve a process of changing the perception into appropriate manners which determine the sojourners" psychological and socio-cultural composing in holistic views.…”
Section: Cross-cultural Adjustmentmentioning
confidence: 99%